Chloroplast genomic characterization and phylogenetic analysis of eleven Persicaria medicinal plants from Guangxi, Southern China - Li, Zhuxin; Dai, Yinghan; Zhai, Shanshan; Cao, Yingying; Cheng, Junyu; Ni, Meng; Song, Lijuan; Tao, Junyu; Zhang, Dapei; Xu, Ziheng; Lai, Yongxing; Tang, Haibo (Frontiers in Plant Science, 2026)
Polygonaceae is widely distributed worldwide, with the genus Persicaria being one of its most medicinally important groups. Nonetheless, genomic research on this genus remains relatively sparse. Moreover, accurate identification of Persicaria species is challenging due to significant morphological variation and similarities, which hinders the development and utilization of their medicinal resources. To address these issues, this study undertook the sequencing, assembly, and annotation of the chloroplast genomes of 11 Persicaria species from Guangxi and reconstructed a phylogenetic tree. The findings reveal that the chloroplast genome lengths of these 11 species range from 159,028 to 161,023 bp, displaying a typical quadripartite structure comprising a large single-copy (LSC) region, a small single-copy (SSC) region, and two inverted repeat (IR) regions. All chloroplast genomes contain four rRNA genes, 30 tRNA genes, and between 74 and 78 protein-coding genes. The codon usage in the chloroplast genomes shows a preference for A or T at the codon endings. The flanking genes at the IR boundaries are highly consistent among the 11 species, indicating that these boundary regions are conserved within the genus Persicaria. Phylogenetic analysis indicates that the 11 species form distinct clades within Persicaria, separate from the genera Calligonum and Fallopia. The findings of this study reveal significant evolutionary conservation and divergence within Persicaria species in Guangxi. The BEAST estimate the stem age of the genus Persicaria to be 81.89 Ma. This research elucidates the phylogenetic positions of these 11 species within Persicaria, offering a scientific foundation for species identification, advancing the understanding of the evolutionary history of the genus in Guangxi, and providing insights into their genetic diversity to support the rational development and utilization of their medicinal resources.